Analysis of Social Feminism Against Novel Banat Riyadh by Raja Al Sanae - Sastro Situmeang (Kajian Linguistik dan Sastra, 2018)
Abstract.Social Feminism expressed by Marxists showed the class gap and the importance of power to women. But it shifted to a more severe realm in all aspects of women's lives. Novel Banat Riyadh gave an overview of four Saudi Arabian girls who seeked to awaken the elements of feminism and reformation for women through the expressions of literary works that became the center of world attention because the facts revealed about the social reality of women was different from what has been understood by the world community today. Therefore, the method used was qualitative with semiotic approach that serves for more complete and detailed research results, using primary data of novel and secondary in the form of books and other scientific works. The result showed that the element of social feminism took place in the character of characters in novels with different backgrounds, education and family rules that restrict and imprison women, dress mode which was considered a reflection of injustice and inequality for women and work structure relation with reality of Arab women social life.Keywords: Social Feminism, Saudi Women, Novel Literature, Social Reality.